2021
DOI: 10.1021/acs.inorgchem.0c03644
|View full text |Cite
|
Sign up to set email alerts
|

Pursuit of an Electron Deficient Titanium Nitride

Abstract: The nitride salt [(PN) 2 Ti≡N{μ 2 -K(OEt 2 )}] 2 (1) (PN − = (N-(2-P i Pr 2 -4-methylphenyl)-2,4,6-Me 3 C 6 H 2 ) can be oxidized with two equiv of I 2 or four equiv of ClCPh 3 to produce the phosphinimide-halide complexes (NPN'), respectively. In the case of 2, H 2 was found to be one of the other products; whereas, HCPh 3 and Gomberg's dimer were observed upon the formation of 3. Independent studies suggest that the oxidation of 1 could imply the formation of the transient nitridyl species [(PN) 2 Ti(≡N•)] (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…Although treatment of 1 with CO and CNAd in the presence of Kryptofix222 and NaN 3 in thf resulted in immediate formation of parent cumulene salts such as NaNCO and NaNCNAd, respectively (confirmed by IR spectroscopy), [17] catalysis was shunned due to the deleterious formation of the parent imide [(PN) 2 Ti(NH)] via an unstable and putative Ti II azide intermediate [K(Kryptofix222)][(PN) 2 Ti(N 3 )]. Previous studies have invoked the extrusion of N 2 from [(PN) 2 Ti(N 3 )] to accompany the formation of a transient nitridyl radical [(PN) 2 Ti(N⋅)], which engages in H‐atom abstraction, most likely from the PN ligand [28] . As a result, a catalytic cycle involving N‐atom transfer from 1 to CO and CNAd is not yet possible due to the inaccesibility of direct formation of titanium nitride anion complex, 1 , rather the detrimental parent imide, 12 is formed (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although treatment of 1 with CO and CNAd in the presence of Kryptofix222 and NaN 3 in thf resulted in immediate formation of parent cumulene salts such as NaNCO and NaNCNAd, respectively (confirmed by IR spectroscopy), [17] catalysis was shunned due to the deleterious formation of the parent imide [(PN) 2 Ti(NH)] via an unstable and putative Ti II azide intermediate [K(Kryptofix222)][(PN) 2 Ti(N 3 )]. Previous studies have invoked the extrusion of N 2 from [(PN) 2 Ti(N 3 )] to accompany the formation of a transient nitridyl radical [(PN) 2 Ti(N⋅)], which engages in H‐atom abstraction, most likely from the PN ligand [28] . As a result, a catalytic cycle involving N‐atom transfer from 1 to CO and CNAd is not yet possible due to the inaccesibility of direct formation of titanium nitride anion complex, 1 , rather the detrimental parent imide, 12 is formed (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have invoked the extrusion of N 2 from [(PN) 2 Ti(N 3 )] to accompany the formation of a transient nitridyl radical [(PN) 2 Ti(N * )], which engages in H-atom abstraction, most likely from the PN ligand. [28] As a result, a catalytic cycle involving N-atom transfer from 1 to CO and CNAd is not yet possible due to the inaccesibility of direct formation of titanium nitride anion complex, 1, rather the detrimental parent imide, 12 is formed (Scheme 3). Despite the parent imido forming from this reaction, we could close the synthetic cycle for N-atom transfer by treating [(PN) 2 Ti-(NH)] with KCH 2 Ph to reform the nitride moiety as shown in Scheme 3.…”
Section: Structural Identification Of the Carbodiimide Motif Onmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41][42][43][44][45] Conversely, early transition-metal nitrides are generally more stable [46][47][48] and in some cases demonstrate nucleophilic reactivity via lled M^N p orbitals or the nitride lone pair. [49][50][51][52][53] Certain metal nitride complexes have been reported to exhibit ambiphilic reactivity, highlighting that subtle modications to the coordination environment and/or redox changes can enable diverse reactivity. 35,[54][55][56] Previous studies by Mayer et al 57,58 and Lau et al 59 have elucidated how changes in ancillary ligands can impact nitride reactivity, work by Holland et al demonstrated that oxidation of both the metal and ancillary ligand (from amide to nitroxide) led to a change from nucleophilic to electrophilic nitride reactivity, 60 and a recent study by Burger and co-workers showed that oxidation of an Ir nitride complex resulted in insertion of the nitride into an aromatic C-C bond of ferrocene.…”
Section: Introductionmentioning
confidence: 99%